2sin2x - 3(sinx + cosx) + 2 = 0
4sinxcosx - 3(sinx + cosx) + 2 = 0
Пусть t = sinx + cosx.
t² = sin²x + cos²x + 2sinxcosx = 1 + 2sinxcosx ⇔ 2sinxcosx = t² - 1
2t² - 2 - 3t + 2 = 0
2t² - 3t = 0
t(2t - 3) = 0
t = 0 или t = 3/2
Обратная замена:
sinx + cosx = 3/2
Разделим на √2
sinx·√2/2 + cos·√2/2 = 3/2√2
sinx·cos(π/4) + cosx·sin(π/4) = √(9/8)
sin(x + π/4) = √(9/8) - нет корней, т.к. sinA ∈ [-1; 1], а √(9/8) > 1.
sinx + cosx = 0
sinx = -cosx
tgx = -1
x = -π/4 + πn, n ∈ Z
Ответ: x = -π/4 + πn, n ∈ Z.